Influences of pH and organic carbon on oxalate removal by alkaliphilic biofilms acclimatized to nitrogen-deficient and supplemented conditions - Weerasinghe Mohottige, T.; Cheng, K.; Kaksonen, A.; Sarukkalige, Priyantha Ranjan; Ginige, M. (Elsevier, 2018)
Accumulation of organic impurities (specifically oxalate) in Bayer liquor is a significant problem for alumina refineries. Microbial degradation is a low-cost solution to the problem, but hostile conditions of Bayer liquor (pH > 14 and nitrogen (N) deficiency) makes it challenging. The solution remains with selection of an appropriate haloalkaliphilic culture and alumina refineries currently have access to two types of bacterial cultures (N-supplemented and N-deficient cultures). To date there is no comparative assessment of the two cultures to examine which one is more suitable to reduce operational risks (i.e. with higher removal efficiencies over a broader range of pH) and costs. Hence, this study compared oxalate removal efficiencies of two packed bed biofilm reactors (N-supplemented and N-deficient) on exposure to a range of influent pH and simple organic compounds. Both reactors were operated (>265 days) at pH 9 and pH influence was compared in batch experiments. Results suggested that both biofilms could tolerate a broad pH range (7–10). The optimal specific oxalate removal rate of N-supplemented reactor was restricted to pH 9, whereas the maximal rate was maintained over a wider pH range (7–8) in N-deficient reactor. In this range, the N-deficient system outperformed the N-supplemented system (105 vs. 130 mg-oxalate/h.g-biomass). Although acclimatised primarily with oxalate, both biofilms simultaneously oxidised other organics (acetate, formate, malonate and succinate) without a noticeable influence on oxalate removal. This study suggests that N-deficient systems are more versatile and better suited to remove organic impurities in Bayer liquor.